Evaluation of Compatibility and Effectiveness of Fungal Lipase Crude Extract from Avocado as an Eco-Friendly Biodetergent - Sedijani, Prapti; Kusmiyati, Kusmiyati; Sukarso, AA; Muhidayani, Respi Eka (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chemical detergents may have negative impacts on both the environment and human health. The addition of enzymes to detergents can help reduce these effects. Therefore, discovering new enzyme sources that are compatible with commercial detergents and can enhance their cleaning performance may provide an ideal solution to this issue. This study aimed to evaluate the compatibility and effectiveness of a crude fungal lipase extract isolated from avocado flesh (AIF) when combined with commercial detergents, as well as to assess its potential in reducing the required amount of chemical detergent. Compatibility tests were conducted by comparing the washing performance of three commercial detergent brands, while effectiveness was evaluated based on washing performance under various detergent concentrations. The results showed that the crude fungal lipase extract was compatible with all tested detergents and had the potential to reduce chemical detergent usage by up to 50%.